2011
DOI: 10.1021/ar2001606
|View full text |Cite
|
Sign up to set email alerts
|

NMR in Metabolomics and Natural Products Research: Two Sides of the Same Coin

Abstract: Small molecules are central to biology, mediating critical phenomena such as metabolism, signal transduction, mating attraction, and chemical defense. The traditional categories that define small molecules, such as metabolite, secondary metabolite, pheromone, hormone, and so forth, often overlap, and a single compound can appear under more than one functional heading. Therefore, we favor a unifying term, biogenic small molecules (BSMs), to describe any small molecule from a biological source.In a similar vein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
196
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(197 citation statements)
references
References 54 publications
(124 reference statements)
1
196
0
Order By: Relevance
“…Biomarker targeting has been used to discover bioactive molecules associated with a variety of specific conditions (Robinette et al, 2012). An example in mice is DB, which was first identified as a testosterone-level dependent urinal biomarker (Novotny et al, 1984) and then later confirmed as a pheromone through behavioural bioassays (Novotny et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker targeting has been used to discover bioactive molecules associated with a variety of specific conditions (Robinette et al, 2012). An example in mice is DB, which was first identified as a testosterone-level dependent urinal biomarker (Novotny et al, 1984) and then later confirmed as a pheromone through behavioural bioassays (Novotny et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Purification of metabolites is usually required for structure elucidation, however, recently, several metabolites have been identified and structurally characterized using NMR without having been isolated in pure form 135) . 2D-NMR analysis of unpurified extracts can also be used to investigate an organisms' metabolome 136) . Differential analysis by 2D-NMR spectroscopy (DANS) 137,138) was employed to examine the gliotoxin biosynthesis pathway (gli) in A. fumigatus, which revealed many new gli-dependent metabolites 139) .…”
Section: -2 Methods Of Analysismentioning
confidence: 99%
“…While the concept of homo-and hetero-covariance spectroscopy was developed nearly three decades ago, there are relatively few reports on the use of synchronous and asynchronous spectra involving NMR spectroscopy [3,14,55,58,59]. In contrast, an abundant number of investigations have applied so-called statistical hetero-spectroscopy (STOCSY) that has delivered important contributions to the field of metabolomics and whose variants have recently been depicted like a phylogenetic tree [22,32,60]. In the current report, the focus is however laid on examples from chemical processes rather than metabolomics.…”
Section: Applications Of Homo-and Hetero-covariance Spectroscopymentioning
confidence: 99%